Epidermolytic hyperkeratosis: a rare case - Pan, Koushik; Chakrabarti, Subrata; Choudhury, Rajdip; Sarkar, Anup; Mitra, Ritabrata (International Journal of Research in Medical Sciences, 2017)
A 6 month old girl presented with generalized hyperkeratosis, most marked over the flexures since birth. On the basis of the clinical& histopathologic findings, she was diagnosed as a case of epidermolytic hyperkeratosis .She was treated with retinoid therapy. Epidermolytic hyperkeratosis (EHK) is an uncommon form childhood keratinizing disorder. Early in life it is associated with generalized blistering and erythroderma. Later on, it produces rippled type of hyperkeratosis. The purpose of this report is to highlight the features of this rare case.